A new species of Acrocomia (Arecaceae) from Central Brazil - Vianna, Suelen Alves (Phytotaxa, 2017)
A new palm species is described in detail, including the morphological characteristics and the leaf anatomy that distinguish it from other species of the genus. Acrocomia corumbaensis has an arborescent habit similar to A. aculeata, A. crispa, A. intumescens and A. totai, however with an inflorescence of a different color, flowers that are green when mature, smaller fruits and seeds. Its leaf anatomy reveals structures similar to those in the other Acrocomia species indicating its position in the genus, but with distinct particularities.